Two-dimensional simulation of liquid metal spray deposition onto a complex surface: II. Splashing and redeposition - Djuric, Z; Grant, P (2001)
A two-dimensional model of liquid metal spray deposition on an arbitrary surface was extended to include the important processes of splashing of spray droplets during collision with the surface, and the subsequent redeposition of scattered material. The extended model was applied in several cases and the simulations compared with experimental results. By including or excluding droplet splashing effects, it was possible to analyze the importance of redeposition both in simulations and experiments. Using the results, it was possible to predict where direct spraying dominated deposit growth, and where the subsequent redeposition had a major influence on deposit growth and the final shape.